PENGARUH DAYA TARIK WISATA TERHADAP KEPUASAN WISATAWAN DI TAMAN BUNGA IMPIAN OKURA, DESA WISATA TEBING TINGGI OKURA - Harsinta, Dhiya Clarita; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study aims to identify the effect of Tourism Attraction on Tourist Satisfaction at The Okura Dream Flower Park, Tebing Tinggi Okura Tourism Village. This research uses an associative quantitative approach. Data collection was carried out using observation, documentation, and questionnaires distributed to tourists who had visited the flower park using accidental sampling techniques. Data analysis includes validity test, reliability test, classical assumption test, simple linear regression analysis, and hypothesis testing. The results showed that there was a significant influence between Tourism Attraction on Tourist Satisfaction in The Okura Dream Flower Park, Tebing Tinggi Okura Tourism Village. This is evidenced by the coefficient of determination (R Square) of 0.866, which shows that Tourism Attraction is able to explain 86.6% of variations in tourist satisfaction while the remaining 13.4% is influenced by other variables outside this regression equation or other variables not examined. Keywords: tourist attraction, tourist satisfaction